PEMBIMBINGAN 8 SNP PADA GURU PAUD DALAM RANGKA PERSIAPAN AKREDITASI DI KECAMATAN PALANG KABUPATEN TUBAN - Ririn Indarwati (Pusat Riset dan Inovasi Nasional, 2023)
Accreditation is a solution for early childhood education, which varies widely, but there are still many PAUD institutions that have not registered for accreditation. One of the causes of PAUD not having accreditation is a lack of understanding of assessment instruments. The purpose of this activity is: to conduct training for PAUD teachers to increase knowledge in preparing for accreditation based on national education standards. The approach taken is educative with the method of discussion and brainstorming. The target of the activity: 19 PAUD teachers, the majority of whom have undergraduate education, with an average work experience of 5.7 years. The material provided was about the importance of accreditation, and shared perceptions about filling in standards 1 to 8, followed by a document review. Evaluation of activities was carried out qualitatively by observing the enthusiasm of the participants in asking questions to the presenters and quantitatively by looking at the knowledge scores before and after coaching. The knowledge score before coaching is 56 and the score after coaching is 82. Increased knowledge is expected in line with the readiness of each institution to apply for accreditation